KINERJA APARATUR PEMERINTAH DESA DALAM PELAYANAN PUBLIK DI DESA SIFAOROASI KECAMATAN HURUNA KABUPATEN NIAS SELATAN - HALAWA, DARMAN KASIH; MANALU, DIMPOS; SIAGIAN, NALOM (JURNAL ILMIAH SIMANTEK, 2023)
This research was motivated by various complaints from the community regarding the services provided by Sifaoroasi village government officials. This can be seen from various existing management elements, where their performance is still not optimal and not in accordance with what the local community expects. This research aims to describe and analyze the performance of Sifaoroasi village government officials, Huruna District, South Nias Regency. This research uses qualitative research methods with a descriptive approach. In this case, all elements of this research are directed at providing information on questions through interviews. Based on the results of the research, the performance of the Sifaoroasi village government apparatus, Huruna District, South Nias Regency, which was studied from several indicators such as service quality and responsiveness, the performance of the village government apparatus has been running well, but the level of productivity, responsibility and accountability of performance is still not optimal or low, and is supported by The results of interviews with research informants greatly influence their level of performance. The inhibiting factors include the lack of human resources, inadequate facilities and infrastructure and lack of discipline among village government officials. The policy recommendation given is that Sifaoroasi village government officials need to optimize performance by increasing and improving the quality of work, implementing time planning at work and carrying out training and coaching as well as regular evaluations.